CAPNET sets sail - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Unexpectedly large numbers of people attended the first Annual Conference on Publishing in the Caribbean, held in Montego Bay, Jamaica, from 31 October to 4 November 2001. More than100 delegates from 26 countries attended, signifying strong...